Evaluating Fracture Resistance And Failure Modes Of Root Filled Teeth Restored With CAD/CAM-Fabricated Post And Core - Alkhatri R; Saleh ARM; Kheder W (Dove Medical Press, 2019)
Reem Alkhatri,1 Abdul Rahman Mohammed Saleh,1 Waad Kheder2 1Department of Restorative Dentistry, Ajman University, Ajman, United Arab Emirates; 2College of Dental Medicine, University of Sharjah, Sharjah, United Arab EmiratesCorrespondence: Abdul Rahman Mohammed SalehAjman University, PO Box 346, Ajman University Street, Aljurf, Ajman, United Arab EmiratesTel +971 4 50228 3188Fax +971 4 670 56874Email rm.saleh@ajman.ac.aeObjective: The aim of this study was to measure the fracture resistance and failure modes of root-filled teeth restored with three different computer-aided design/computer-aided manufacturing (CAD/CAM)-fabricated post and core assemblies.Methods: Thirty extracted intact maxillary central incisors were used in the study, and the teeth were endodontically treated and sectioned to a root length of 16 mm. The samples were divided into three groups (n = 10) according to the mean of the dimensions at the cervical portion of the root. The posts and cores were fabricated with CAD/CAM technology using metal, zirconia, and polymer-infiltrated ceramic network (PICN) material. The posts were luted using resin cement, and then, metal crowns were fabricated, cemented, and then subjected to a compression to determine the fracture resistance force. Fracture of the post and core or fracture of the root above the level of the acrylic resin was considered as a favorable fracture, while nonfavorable fractures were those where the root fracture occurred below the level of the acrylic resin. Statistical analysis was carried out using SPSS software, and one-way analysis of variance was used to analyze root fracture resistance in Newton. The number of failure modes, post–core fractures and/or root fractures was calculated. The differences between study groups were revealed using the chi-square test.Results: The results of ANOVA revealed a nonsignificant difference in the resistance to fracture among the study groups (P = 0.114). The failure modes were nonfavorable for all metal and zirconia samples and seven PICN samples. However, three PICN samples exhibited a favorable represented by core fracture without root fracture.Conclusion: There was no significant difference between metal and zirconia samples in terms of nonfavorable fracture, while few PICN samples exhibited a favorable fracture. PICN material can be used in the fabrication of post and core assemblies using CAD/CAM.Keywords: CAD/CAM, cast post, PICN, failure mode